IMPROVING GRADE VIII STUDENTS™ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH BRAINSTORMING TECHNIQUE - Manalu, Febrina -; Sinaga, Lidiman - (Universitas Negeri Medan, 2014)
Abstract The objective of this study is to find out whether Brainstorming Technique can improve students™ Achievement in writing. This study was conducted by using classroom action research. The subject of this research was the second year students of SMP VIII-2 Swasta HKBP Sidorame Medan. The research was conducted in two cycles. The first cycle was three meetings and the second cycle was also three meetings. The instruments for collecting data used writing test for quantitative data and used diary notes, interview sheet and observation sheet for qualitative data and the qualitative data showed that the students were interested in applying Brainstorming technique. Based on the writing test result, the students™ score kept improving in every test. In orientation test, the mean score was 65.50. In the test of cycle 1 the mean score was 73.33 and the mean score in the test of cycle 2 was 79.97. In line with the data, it was found that the Brainstorming technique can improve students™ writing achievement. Keywords: Writing, Writing Assessment, Brainstorming, Classroom Action Research